Flexural behavior of high-performance concrete beams using finite element analysis - Khadiranaikar, R.B.; Nageshkumar, S.; Muranal, S.M.; Awati, M.M. (Journal of Structural Engineering, 2025)
The finite element modeling (FEM) is being used to study the normal strength reinforced concrete elements, as laboratory based physical testing of elements has some limitations. But, the FE analysis of High Performance Concrete (HPC) elements is difficult because of characterization of material properties. In view of this, study of the flexural behaviour of HPC beams with strength range of 40-100 MPa was carried out using FEM package ANSYS. The flexural behavior predicted using ANSYS was compared with experimental and theoretical results. The ANSYS results show variation of 2 to 8 percent when compared with experimental results and theoretical calculations.